Effect of supplementing multiparous sows with xylanase, L-Carnitine and their combination during maternity on litter performance and survivability of piglets - Jith John Mathew; M.T. Dipu; K. AllyI; K. Lalu; R. Thirupathy Venkatachalapathy; Justin Davis (Journal of Veterinary and Animal Sciences, 2025)
A nutritional study was conducted using 24 multiparous Large White Yorkshire (LWY) sows maintained at the Centre for Pig Production and Research (CPPR), Mannuthy from 75th day of gestation till weaning (42nd day of farrowing) to evaluate the effect of supplementing feed additives during maternity on litter performance and survivability of piglets. Experimental animals were grouped into four dietary treatments of six animals each, following the completely randomised design. Control diet (C) was formulated as per NRC, 2012 (3300 kcal MEkg feed and 18 per cent crude protein). The other three dietary treatments were prepared by fortification of C with additives viz., L-Carnitine at 50 mgkg diet (Cc), xylanase at 0.01 per cent level (Cx) and a combination of both L-Carnitine at 50 mgkg diet and xylanase at 0.01 per cent level (Ccx). All sows received experimental diets from the 75th day of gestation to four weeks after farrowing. The experimental animals were maintained on farm rations until weaning, thereafter. Litter size and litter weight were recorded at birth and weekly intervals until weaning. All observed indices on litter performance did not differ among the four treatment groups. Average piglet weight and survivability did not differ among the four dietary treatment groups during the first recording during the experiment, as well as during the last recording at the weaning stage. From the overall results of the experiment, it could be inferred that supplementation of maternal diets with L- L-Carnitine at 50 mg kg diet or xylanase at 0.01 per cent level or the combination of both could not improve the overall litter performance and survivability of LWY piglets.